Keadilan dan Pemerataan Ekonomi Melalui Konsep Baitul Mal wat Tamwil (BMT) - Fauzi Muhammad (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2020)
Baitul Mal wat Tamwil (BMT) is a sharia microfinance institution that is conceptually held for non-profit muslims. In collecting funds and channeling based on sharia principles, the problems are resolved in the religious court. Judging from the aspect of economic justice, it is not very different from other financial institutions, only the BMT management target dives more on the potential of zakat, infaq and sedeqah that favor the helpless dhu'afa to be empowered, from consumptive to productive and having resilience with populist based financial management and amaliyah value.